W Sprawie Nieskończonej Tarczy Częściowo Obciążonej w Otworze Kołowym - Mikołajczyk, H. (Engineering Transactions, 1962)
The paper contains a closed-form solution of the problem of the infinite plate partially loaded on the edge of a circular hole. The solution is obtained by means of Fourier series, making use of the general solution obtained by N.J. MUSKHELISHVILI, [2]. The resulting stress distribution is illustrated by means of a numerical example in the form of graphs.